Effect of a high dose atorvastatin as added-on therapy on symptoms and serum AMPK/NLRP3 inflammasome and IL-6/STAT3 axes in patients with major depressive disorder: randomized controlled clinical study - Aldossary, Khlood Mohammad; Ali, Lashin Saad; Abdallah, Mahmoud S.; Bahaa, Mostafa M.; Elmasry, Thanaa A.; Elberri, Eman I.; Kotkata, Fedaa A.; El Sabaa, Ramy M.; Elmorsi, Yasmine M.; Kamel, Mostafa M.; Negm, Walaa A.; Elberri, Aya Ibrahim; et al. (Frontiers in Pharmacology, 2024)
Background: Neuroinflammation pathways have been associated with the development of major depressive disorders (MDD). The anti-inflammatory characteristics of statins have been demonstrated to have significance in the pathophysiology of depression. Aim: To investigate the mechanistic pathways of high dose atorvastatin in MDD. Patients and Methods: This trial included 60 patients with MDD who met the eligibility requirements. Two groups of patients (n = 30) were recruited by selecting patients from the Psychiatry Department. Group 1 received 20 mg of fluoxetine plus a placebo once daily. Group 2 received fluoxetine and atorvastatin (80 mg) once daily. All patients were assessed by a psychiatrist using the Hamilton Depression Rating Scale (HDRS). A HDRS score of ≤ 7 indicates remission or partial remission [HDRS<17 and>7]. Response was defined as ≥ 50% drop in the HDRS score. The serum concentrations of nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP-3), interleukin-6 (IL-6), adenosine monophosphate activated protein kinase (AMPK), and signal transducer and activator of transcription factor-3 (STAT-3) were measured. Results: The atorvastatin group showed a significant reduction in the levels of all measured markers along with a statistical increase in the levels of AMPK when compared to the fluoxetine group. The atorvastatin group displayed a significant decrease in HDRS when compared to its baseline and the fluoxetine group. The response rate and partial remission were higher in the atorvastatin group than fluoxetine (p = 0.03, and p = 0.005), respectively. Conclusion: These results imply that atorvastatin at high doses may be a promising adjuvant therapy for MDD patients by altering the signaling pathways for AMPK/NLRP3 and IL-6/STAT-3.